Understanding populist party organisation : the radical right in Western Europe - Heinisch, Reinhard Rudolf 1942- HerausgeberIn; Mazzoleni, Oscar 1968- HerausgeberIn; Heinisch, Reinhard 1963- HerausgeberIn (Palgrave studies in European political sociology, 2016)
The Austrian Freedom Party : organizational development and leadership change / Reinhard Heinisch -- The Vlaams Belang : party organization and party dynamics / Emilie van Haute and Teun Pauwels -- The Swiss People's Party : converting and enhancing organization by a new leadership / Oscar Mazzoleni and Carolina Rossini -- The Italian Lega Nord / Duncan McDonnell and Davide Vampa -- The French Front National : organizational change and adaptation from Jean-Marie to Marine Le Pen / Gilles Ivaldi and Maria Elisabetta Lanzone -- The Norwegian Progress Party : between a business firm and a mass party / Anders Ravik Jupskås -- The Sweden Democrats / Ann-Cathrine Jungar -- Comparing populist organizations / Reinhard Heinisch and Oscar Mazzoleni